Development of Elementary Linear Algebra Learning Video Media in Islamic Context - Mattoliang, Lisnasari Andi; Majid, Ahmad Farham; Hasan, Rezkianti; Baharuddin, Baharuddin; Nur, Fitriani (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
The development of online learning is increasingly rapid, especially during the Covid-19 pandemic which demands an innovation in the education system. However, this development is not accompanied by the availability of innovative learning media. Therefore, this study aims to develop an elementary linear algebra learning video media in Islamic context. This research type is research and development using a 4D development model consisting of 4 stages, namely define, design, develop, and disseminate. The subjects of this research trial were students of the Department of Mathematics Education, class of 2020 B, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. The research data were obtained using questionnaires, observations, and learning outcomes tests. The data is processed through the analysis of validity, practicality, and effectiveness. The results showed that the video media that had been developed had met the criteria of being valid, practical, and effective. Thus, this learning video media can be a solution to better support the implementation of online learning.Perkembangan pembelajaran daring semakin pesat khususnya di masa Pandemi Covid-19 yang menuntut adanya inovasi sistem pendidikan. Namun, perkembangan ini tidak diiringi dengan ketersediaan media pembelajaran yang inovatif. Karena itu, penelitian ini bertujuan untuk mengembangkan media video pembelajaran aljabar linear elementer dalam konteks Islam. Jenis penelitian ini adalah penelitian dan pengembangan (research and development) dengan menggunakan model pengembangan 4D yang terdiri dari 4 tahapan yaitu define, design, develop, dan disseminate. Subjek uji coba penelitian ini adalah mahasiswa Jurusan Pendidikan Matematika, angkatan 2020 kelas B, Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. Data penelitian diperoleh dengan menggunakan angket, observasi, dan tes hasil belajar. Data diolah melalui analisis kevalidan, kepraktsian, dan keefektifan. Hasil penelitian menunjukkan bahwa media video pembelajaran aljabar linear elementer dalam konteks Islam yang dikembangkan telah memenuhi kriteria valid, praktis, dan efektif. Dengan demikian, media video pembelajaran ini dapat menjadi solusi untuk mendukung terlaksananya pembelajaran daring dengan lebih baik.